ADVANCING COLON-TARGETED BUDESONIDE DELIVERY: A REVIEW OF THE LATEST DEVELOPMENTS AND FUTURE PERSPECTIVES - AMIT KUMAR; GUNJAN DHIRWAN; PRANSHU TANGRI; YOGITA TYAGI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Colon-specific drug delivery is advantageous for treating various local diseases, including inflammatory bowel disease, ulcerative colitis, Crohn’s disease, chronic pancreatitis, and colonic cancer. Corticosteroids are considered as the first line drug therapy for the treatment of colon specific diseases, but also causes adverse side effects. Budesonide, a second-generation corticosteroid characterized by a relatively low side effect profile and low bioavailability resulting from extensive first-pass liver metabolism, has received approval from the Food and Drug Administration for the treatment of colon-specific diseases. Various methods have been employed for colon-targeted drug delivery. Key approaches include pH-sensitive drug delivery, time-controlled delayed release, and microbially triggered drug delivery, along with additional strategies such as prodrug delivery and pressure-controlled drug delivery. Budesonide can be given by many different formulations like coated tablets, multi-matrix tablets, pellets-based formulations, capsules, 3D-printing and nanoparticles-based formulation techniques. This detailed analysis in budesonide can help to improve the development of new techniques and treatments for colon specific drug delivery.